The iberian Dea Mater: iunstir and the cult of the planet Venus in the Iberian world - Iborra Pellín, Daniel (Complutum, 2024)
In recent years, astronomical orientations to the planet Venus have been valued in temples and sacred caves of the Iberian Culture. These testimonies ask to know what the name of this divinity would be. This article relates astronomical, iconographic and linguistic data that indicate the possibility that the name of the Iberian Dea Mater was Iunstir. This goddess epithet could be formed by the terms iun (goddess-name) and stir (“star”), as the sumerian goddess Ishtar or the phoenician Astart. This hypothesis suggests that the name of the Iberian Dea Mater would be Iun / Iunstir.